2011
DOI: 10.1002/jbm.a.33093
|View full text |Cite
|
Sign up to set email alerts
|

Degradation, cytotoxicity, and biocompatibility of NIPAAm‐based thermosensitive, injectable, and bioresorbable polymer hydrogels

Abstract: A thermosensitive, injectable and bioresorbable polymer hydrogel, Poly(N-isopropylacrylamide-co-dimethyl-γ-butyrolactone acrylate-co-acrylic acid) (poly(NDBA)), was synthesized by radical copolymerization with 7.00 mol.% dimethyl-γ-butyrolactone acrylate in tetrahydrofuran (THF). The chemical composition was determined by acid titration in conjunction with 1H NMR quantification. The molecular weight and polydispersity were determined by gel permeation chromatography (GPC) in conjunction with static light scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 32 publications
2
53
0
1
Order By: Relevance
“…Additionally the attached SILY, combined with the electrostatic attraction between the KAFAK and the particle, could hinder the release of any KAFAK that was successfully loaded into the core, resulting in the incomplete peptide release that was observed with these particles. Work has been done, in our lab and others, on the synthesis of degradable poly(NIPAM) nanoparticles (55)(56)(57)(58)(59)(60), and it is likely that the use of a similar system in these particles would result in a more complete peptide release profile over a longer time period.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally the attached SILY, combined with the electrostatic attraction between the KAFAK and the particle, could hinder the release of any KAFAK that was successfully loaded into the core, resulting in the incomplete peptide release that was observed with these particles. Work has been done, in our lab and others, on the synthesis of degradable poly(NIPAM) nanoparticles (55)(56)(57)(58)(59)(60), and it is likely that the use of a similar system in these particles would result in a more complete peptide release profile over a longer time period.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have demonstrated that this hydrogel exhibited an LCST of 27°C and a swelling ratio of 150% before degradation. However, mass remaining reduced to 0 in 20 days both in vitro 27 and in vivo, 28 due to the hydrolysis of DBA leading to an increase of LCST. The rapid degradation ratio is detrimental to the adhesion and proliferation of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…299,[305][306][307][308][309][310] However, PNIPAM notably shows cytotoxity and is non-biodegradable, 311 which limits its applications in vivo, even though PNIPAM with finite molecular weight can be eliminated via glomerular filtration without in vivo long-term accumulation. To overcome these drawbacks, PNIPAM hydrogels have been established as cell sheets to construct organized hepatocyte or endothelial mono-or multi-layers.…”
Section: Peg and Poly(n-isopropylacrylamide)mentioning
confidence: 99%